Larangan Pendidikan Formal bagi Kaum Perempuan di Afghanistan: Tinjauan Hadis al- Bukhari Nomor Indeks 7310 tentang Kesetaraan Gender - Rodina Billah; Andris Nurita; Muhid Muhid (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
Afghanistan is one of the countries with relatively high cases of discrimination against women. This is due to the implementation of the Islamic shari'a system of government imposed by the Taliban based on their own understanding. As well as textual interpretation of some of the postulates of Islamic teachings. So that the existence of the role of women is increasingly cornered. One of the Taliban's policies, which is considered to violate human rights, is the prohibition of higher education for women in Afghanistan. This problem raises the negative stigma of "outsiders" towards Islam, they will consider Islam as a religion that mistreats women. In fact, the Islamic sharia law implemented by the Taliban is different from the essential teachings of Islam. The reason is that there are so many verses of the Qur'an or Hadiths that explain gender equality, one of which is the Hadith narrated by al-Bukhari index number 7310 which explains the attitude of the Prophet Muhammad SAW, related to education for women. In this context, this research using the Library research method aims to provide a review of the case of the prohibition of education for women that occurred in Afghanistan and its relationship with the Hadith narrated by Imam al-Bukhari number 7310. The hadith is one of the arguments that women also have rights in education. To achieve the purpose of this study, it is necessary to analyze Hadith Imam al-Bukhari no. 7310 in order to describe and interpret a case of prohibition of higher education for women. This research concludes that the prohibition of education that has occurred in Afghanistan is a form of patriarchal culture that is considered as an act that has been legitimized by Islamic religious propositions, as well as an understanding that is only limited to the textual propositions of Islamic teachings.